Fate decisions of breast cancer stem cells in cancer progression - Xu, Hui; Zhang, Fengxia; Gao, Xiaokang; Zhou, Qiwang; Zhu, Linhai (Frontiers in Oncology, 2022)
Breast cancer has a marked recurrence and metastatic trait and is one of the most prevalent malignancies affecting women's health worldwide. Tumor initiation and progression begin after the cell goes from a quiescent to an activated state and requires different mechanisms to act in concert to regulate t a specific set of spectral genes for expression. Cancer stem cells (CSCs) have been proven to initiate and drive tumorigenesis due to their capability of self-renew and differentiate. In addition, CSCs are believed to be capable of causing resistance to anti-tumor drugs, recurrence and metastasis. Therefore, exploring the origin, regulatory mechanisms and ultimate fate decision of CSCs in breast cancer outcomes has far-reaching clinical implications for the development of breast cancer stem cell (BCSC)-targeted therapeutic strategies. In this review, we will highlight the contribution of BCSCs to breast cancer and explore the internal and external factors that regulate the fate of BCSCs.